Medical Students' Career Choice and Attitudes Toward Psychiatry: Case of the Czech Republic - Motlová, Lucie Bankovská; Janoušková, Miroslava; Formánek, Tomáš; Goetz, Michal; Holub, David; Hubeňák, Jan; Kašpárek, Tomáš; Látalová, Klára; Papežová, Hana; Světlák, Miroslav; Šilhán, Petr; Trančík, Pavel; et al. (Academic psychiatry, 2020)
OBJECTIVE: A survey among medical students of all medical schools in the Czech Republic was conducted to investigate attitudes and views of psychiatry and career choice of psychiatry. METHODS: A Czech version of the Attitudes to Psychiatry Scale (APS) and a questionnaire surveying demographic characteristics and choices of future specialty were distributed to all medical students of eight medical schools in the Czech Republic via the schools' internal communication systems in the form of an anonymous online questionnaire. RESULTS: Out of a total of 10,147 medical students in the Czech Republic (academic year 2019/2020), 2418 students participated in the survey (response rate 23.8%). Psychiatry as a non-exclusive career choice was considered by 31.3% respondents; child and adolescent psychiatry was considered by 15.4% respondents. Psychiatry as the only choice was considered by 1.6%, and child and adolescent psychiatry was not considered at all. The interest in both specialties was declining since the first year of study. The status of psychiatry among other medical specialties was perceived as low; students were rather discouraged from entering psychiatry by their families. They did not feel encouraged by their teachers to pursue career in psychiatry despite the fact that they were interested in psychiatry. They also felt uncomfortable with patients with mental illness. CONCLUSIONS: Despite high enthusiasm for psychiatry in the first year of medical school, only a small proportion of medical students consider to choose psychiatry, and especially child and adolescent psychiatry, as a career at the end of medical school.
Keywords: Attitude; Child and adolescent psychiatry; volba povolání; průzkumy a dotazníky; dítě; Stigma; postoj zdravotnického personálu; Surveys and Questionnaires; Adolescent; lidé; postoj; Students, Medical; Attitude of Health Personnel; Career choice; studenti lékařství; Czech Republic; Career Choice; Česká republika; Child; psychiatrie; mladiství; Psychiatry; Undergraduate training; Humans